2018
DOI: 10.1177/1076029618792302
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of VKORC1-1639 in Children With Intracranial Hemorrhage Due to Vitamin K Deficiency

Abstract: Intracranial hemorrhage due to vitamin K deficiency is a serious disease that can lead to morbidity, mortality, and mental retardation. Our goal in this study is to determine the frequency of VKORC1-1639 G>A polymorphism in patients who have undergone intracranial hemorrhage due to vitamin K deficiency bleeding (VKDB). To study VKORC1-1639 G>A polymorphism, blood was drawn from patients (n = 51, age 8:0 ± 6:5 years) followed at the Pediatric Neurology and Hematology section, Faculty of Medicine, Erciyes Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several reports have revealed that genetic factors can influence the vitamin K-dependent coagulation system and intraventricular hemorrhage [14,15]. Further studies regarding the usefulness of testing for genetic variants to prevent and diagnose VKDB are warranted.…”
Section: Diagnosis Of Vkdb In Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have revealed that genetic factors can influence the vitamin K-dependent coagulation system and intraventricular hemorrhage [14,15]. Further studies regarding the usefulness of testing for genetic variants to prevent and diagnose VKDB are warranted.…”
Section: Diagnosis Of Vkdb In Infancymentioning
confidence: 99%
“…Polymorphisms in VKORC1 (G-1639A) and coagulation factor 7 (F7-323 Ins10) were reportedly associated with intraventricular hemorrhage or low factor VII levels [14]. Recently, the presence of variant alleles in VKORC1 (SNP: rs9923231) was reportedly associated with vitamin K deficiency bleeding (VKDB) [15]. Although reports that suggest a relationship between VKORC1 genetic variants and VKDB in Japan are lacking, the low enzyme activity of vitamin K epoxide reductase might be associated with VKDB in infancy because of the ethnic differences in the incidence of VKDB in infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Whether these polymorphisms have a functional effect on vitamin Kdependent coagulation factors remains to be seen. 7,[9][10][11] Although the index child did not suffer intracranial bleed, he did require a second dose of parenteral vitamin K at 9 weeks due to deranged coagulogram. Traditional 1 mg intramuscular prophylaxis gives almost complete protection against VKDB.…”
Section: Discussionmentioning
confidence: 99%
“… Unal et al (2014) described that a newborn presented with intracranial bleeding had a mutation of T903C in PROC . Other genes related to perinatal and pediatric ICH including VKORC1 (encoding vitamin K epoxide reductase complex subunit 1) ( Berber et al, 2018 ), F10 (encoding FX) ( Herrmann et al, 2005 ), and F13 (encoding FXIII) ( Göpel et al, 2002 ; Table 5 ).…”
Section: Genetic Variants Associated With Perinatal and Pediatric Ichmentioning
confidence: 99%